Applications of Generative Artificial Intelligence in Medical Imaging: A Review of Opportunities and Risks - Chen, Zhouyu (Exploring Science Academic Conference Series, 2026)
Generative Artificial Intelligence (GAI), with its core capabilities in image synthesis, data augmentation, and cross-modal transformation, is profoundly reshaping the entire workflow of medical imaging, including acquisition, diagnosis, treatment planning, and ed ucation and training. This paper systematically reviews the technical pathways and clinical application progress of generative AI in the field of medical imaging. It focuses on analyzing its core value in improving imaging quality, alleviating data scarcity, assisting precision diagnosis and treatment, and empowering primary healthcare. At the same time, it deeply explores potential risks such as “medical hallucination” misleading, black -box effects, data bias, and lagging compliance regulation. On this bas is, the paper proposes development strategies emphasizing compliance, standardization, and strong interpretability, aiming to provide theoretical references for the safe implementation and large-scale promotion of generative AI in the field of intelligent medical imaging.